Duodenal atresia with familial apple peel syndrome: case study with review of literature - Kirtane, Jyotsna M (BMJ Case Rep, 2019)
This is a case report of a neonate who was antenatally diagnosed with jejunal atresia which turned out to be duodenal atresia with apple peel syndrome. A previous sibling, who also had apple peel but with jejunal atresia, succumbed to sepsis after surgery. The first sibling had jejunal stenosis and had died of sepsis following surgery. Combination of duodenal atresia with apple peel is extremely rare. This coupled with a familial condition is rarer still. This case was challenging due to the short length of the gut and prolonged need for total parenteral nutrition and sepsis in postoperative period.